2006
DOI: 10.1111/j.1743-6109.2006.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Dose Relative to Sexual Intercourse Attempt in Previous Sildenafil Citrate Users Treated with Tadalafil

Abstract: Objectives Tadalafil, a phosphodiesterase type 5 inhibitor, has an extended period of effectiveness, up to 36 hours, for the treatment of erectile dysfunction (ED). Changes in behavior of long-term sildenafil users were evaluated by assessing time of dose relative to sexual intercourse attempts during treatment with sildenafil and tadalafil. Materials and Methods This open-label study was conducted in men with ED and a histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Eighty-two percent of the patients who changed treatment from another PDE5 inhibitor reported remaining on tadalafil after 1 year, with improvement in ED severity. This observation is consistent with a similar response to tadalafil observed in naïve patients and sildenafil prior responders [35], and a change in timing of sexual intercourse relative to dose in previous sildenafil users treated with tadalafil [22] that may translate in preference for tadalafil vs. sildenafil as shown in a crossover study [24,36] as well as switch study [37].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Eighty-two percent of the patients who changed treatment from another PDE5 inhibitor reported remaining on tadalafil after 1 year, with improvement in ED severity. This observation is consistent with a similar response to tadalafil observed in naïve patients and sildenafil prior responders [35], and a change in timing of sexual intercourse relative to dose in previous sildenafil users treated with tadalafil [22] that may translate in preference for tadalafil vs. sildenafil as shown in a crossover study [24,36] as well as switch study [37].…”
Section: Discussionsupporting
confidence: 84%
“…At baseline, responses to the International Index of Erectile Dysfunction-erectile function (IIEF-EF) domain were collected [26], together with information on previous treatments for ED and reasons for discontinuation, demographics, concomitant diseases, duration and etiology of ED, relationship history, and expectations of treatment. The IIEF-EF domain score was used to categorize the severity of ED: severe (score 1-10), moderate (score [11][12][13][14][15][16], mild (score [17][18][19][20][21][22][23][24][25], and normal (score Ն 26).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, patients taking tadalafil attempted intercourse up to 36 h after tadalafil dosing when instructed that they could do so (79)(80)(81)108). Data from the recent, 12-month DETErminants of Continued use of Tadalafil (DETECT) study suggested that early success with tadalafil was a determinant of long-term outcomes, including medication adherence (Figure 4; 109).…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…The present study was conducted to examine to what extent prior sildenafil citrate users modify their sexual intercourse and drug intake timing behavior when exposed to tadalafil with respective dosing instructions. Results for the overall study population, which included 2,760 patients from 21 countries, have been published previously [5]. This report reexamines those data by geographical region.…”
Section: Introductionmentioning
confidence: 53%